Investigation and comparative study of double-sided yokeless asymmetric flux reversal permanent magnet linear machine - Shen, Yiming (2024)
This article proposes two types of double-sided yokeless asymmetric flux reversal permanent magnet linear machines (DYAFR-PMLM) for long-distance application. By employing asymmetric excitation, the second-order harmonic magnetomotive force (MMF) arises with significant amplitude, making it a valuable resource for enhancing thrust force density. The article starts by introducing the machine topology and working mechanism under both asymmetric excitation and a complementary secondary structure. Subsequently, the mechanism for thrust force generation under multiple MMFs is analytically calculated and validated by using finite element analysis. Then, some crucial electromagnetic performance metrics, including the open-circuit performances, thrust force performances, power factor and demagnetization risk are comparatively analyzed. The results reveal that the proposed DYAFR-PMLM with a consequent pole (CP) structure can achieve a thrust force density 59% higher than conventional FR-PMLM. Additionally, the power factor can be increased to 0.89, and the normal force can be significantly reduced from kilo-newtons to under 10 newtons. More notably, DYAFR-PMLM attains a thrust force density of 78.2% while substantially reducing the PM volume to about 1/74 over a 10-meter distance in comparison to conventional PMLM. Finally, a prototype of DYAFR-PMLM with a CP structure is fabricated and validated through experimental testing.